Implementasi Akad Qardh dalam Program Baznas Microfinance Masjid di DKM Masjid Syiarul Islam Kuningan - Mualim, Mualim; Matangaji, Amaludin; Ramadhan, Ahmad Ali (Al Barakat, 2025)
The BAZNAS Microfinance Mosque Program, organized by the Mosque Prosperity Council (DKM) of Syiarul Islam Kuningan, focuses on community economic empowerment through the provision of interest-free loans to micro-entrepreneurs. Its primary objective is to assist business actors who struggle to access capital by offering repayable loans according to their financial capacity, without any interest burden. However, the implementation of the qardh contract in this program and its compliance with Islamic law have not been thoroughly examined. This study aims to explore the implementation of the qardh contract and analyse it from the perspective of Islamic jurisprudence. The research uses a qualitative research method with a field research approach, with a semi-structured interview method. Data analysis techniques involve reduction, presentation, and conclusion drawing. The results show that the program applies the qardhul hasan contract as an interest-free business capital loan. Its implementation includes selection, verification, mentoring, and the productive and sustainable distribution of zakat funds, achieved through collaboration between the mosque and zakat institutions. Key findings highlight the use of qardhul hasan without interest or additional fees, accompanied by recommendations for voluntary infaq during repayments. When repayment issues arise, a persuasive approach is adopted through direct communication, payment restructuring, and flexible deadlines. From the standpoint of Islamic law, this practice aligns with sharia principles, including the fulfilment of the pillars and conditions of the akad (contract), the voluntary nature (antaradhin) of the recommended infaq, its freedom from riba (usury), and the resolution mechanisms that reflect the values of taawun (mutual assistance) and justice, as outlined in the Qur'an and Hadith.